Rational programming of polysaccharide-based double network hydrogel with heterogeneous architecture and multifunction via electrical signal/temperature triggered sequential self-assembly. (1st December 2021) - Yan, Kun; Wan, Yekai; Yang, Chenguang; Chen, Yuanli; wei, Wei; Li, Xiufang; Wang, Dong
Abstract : Rational programming of double network hydrogel (DN gel) structure is an effective strategy to acquire satisfied mechanical properties and innovative functions. Herein, we report a novel electrochemically strategy for rational design of a DN gel from the blends of two stimuli-responsive self-assembling polysaccharides chitosan (CS, pH-responsive) and agarose (Agar, thermally responsive) by using externally applied electrical signal/temperature stimulations to cue sequential self-assemblies. Specifically, considering of the remarkable difference in the filed-induced chains' migration behavior at liquid/solid systems, chitosan's electrophoretic deposition (EDP) processes were performed comparably at different temperatures and two types of DN gels were fabricated with dramatically different growing kinetics, tailored crystalline structures and enhanced mechanical properties. Moreover, the bioinspired multilayer structure could be facially imparted in the DN gels by using an oscillating electrical signal, and their great potential applications such as the pH/ethanol-sensitive device or versatile platform for staged drug delivery have been revealed respectively. Eventually, we demonstrated that the electrical signal is highly advantageous in preparing DN gels that able to: (i) provide complex pH cues to guide polymer chains self-assembled with specific patterning structures; (ii) quantitative analysis of the gelation process via transfer charges; (iii) offer great possibilities for hydrogel construction via electric filed-induced chain migration. Therefore, we believe this electro-biochemically synthesizing approach could spur new insight into the multifunctional hydrogel materials constructions and biomedical related applications.